105k views
5 votes
How to solve 3×(6+2)-3+4÷2?


User RichardLiu
by
6.4k points

2 Answers

2 votes

Answer:

23

Explanation:

3×8-3+4-2

24-3+4-2

24-3+4-2

= 23

7 votes

Answer:


\Huge \boxed{23}

Explanation:

Order of operations

PEMDAS

Parenthesis

Exponent

Multiply

Divide

Add

Subtract

Do parenthesis first.


\displaystyle (6+2)=8


\displaystyle 3*8-3+4/2

Then multiply and divide numbers from left to right.


\displaystyle 3*8=24


\displaystyle 24-3+4/2


\displaystyle 4/2=2


\displaystyle 24-3+2

Add and subtract numbers from left to right to find the answer.


\displaystyle 24-3=21


\displaystyle 21+2=23


\huge \boxed{23}, which is our answer.

Hope this helps!

User Jonathanberi
by
6.2k points